Bisphosphonate-induced osteonecrosis of the jaws: a literature review - Teófilo , Nayane de Andrade; Denardin, Caio; da Silva , Thiago Quirino Mota; Margute , Túlio Garcia; Rossato , Andrei Rabenschlag; Maione, Max Soares; Margute , Tiago Garcia; dos Santos , Igor Fonseca (Brazilian Journal of Case Reports, 2021)
Bisphosphonates are widely used, whether in osteoporosis or malignant bone disorders. Therefore, it is necessary that there is sufficient knowledge about the adverse effects of this drug, especially in relation to Osteonecrosis of the Jaws Developed by Bisphosphonates, which is a pathology generated in the gnathic bones. So, the following question was asked in the research problem: What is the current situation regarding the use of bisphosphonates and the onset of osteonecrosis of the jaw? Searches were carried out on digital library websites in search of articles and research in books by renowned authors. Inclusion and exclusion criteria for articles found were defined. The verification of each article was carried out so that it could have perspective and follow-up on the subject discussed. The following databases were used: PUBMED, BIREME and LILACS, and SCIELO between the years 2007 to 2019. It was concluded then that Bisphosphonates play a very important role as a cause of osteonecrosis of the jaws, where the prognosis will be worse if the patient is treated with intravenous rather than oral types.